2017
DOI: 10.1159/000475820
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Aneurysmal Bone Cysts in the Pediatric Population: A Systematic Review of the Literature

Abstract: Cervical spine aneurysmal bone cysts (ABCs) in pediatric patients have not been thoroughly studied. Using PubMed and Google Scholar, a systematic review of the literature was conducted for publications that included patients aged ≤15 years with a confirmed diagnosis of ABC in the cervical spine. Thirty-five studies with a total of 71 patients met the inclusion criteria. Nearly 80% of patients presented with neck or shoulder pain. The axis was the level most frequently involved (34.28%), followed by C5 (24.28%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…ABC may arise from any bone; however, the metaphysis of long bones is the most frequently affected site [5]. Although the cervical region is rarely involved, the presentation of our patient is typical for these cases: in a recent meta-analysis with 71 patients presenting with cervical spine ABC, Protas et al [6] found complaints of neck or shoulder pain in ∼80% of the patients; moreover, posterior elements were involved in 88%, and C2 was the most frequently affected level (34%). In the cervical spine, CT scan usually shows lytic lesions described as honeycomb or an eggshell ballooning of the bone cortex, while MR imaging shows a characteristic fluid-fluid interface on T2W and a heterogeneous appearance on T1W [7].…”
Section: Discussionmentioning
confidence: 66%
“…ABC may arise from any bone; however, the metaphysis of long bones is the most frequently affected site [5]. Although the cervical region is rarely involved, the presentation of our patient is typical for these cases: in a recent meta-analysis with 71 patients presenting with cervical spine ABC, Protas et al [6] found complaints of neck or shoulder pain in ∼80% of the patients; moreover, posterior elements were involved in 88%, and C2 was the most frequently affected level (34%). In the cervical spine, CT scan usually shows lytic lesions described as honeycomb or an eggshell ballooning of the bone cortex, while MR imaging shows a characteristic fluid-fluid interface on T2W and a heterogeneous appearance on T1W [7].…”
Section: Discussionmentioning
confidence: 66%
“…ABCs are rare but benign, highly vascular tumours and account for up to 1% of all bone tumours and 15% of primary spinal tumours 1–4. The majority of ABCs occur in the first two decades of life1–4 and uncommonly affect the cervical spine, with only 71 cases reported in the literature till recently 1…”
Section: Descriptionmentioning
confidence: 99%
“…Fluid-fluid levels, in particular, are strongly suggestive of an ABC 10. However, a plethora of other diseases including giant cell tumour, eosinophilic granuloma, fibrous dysplasia, unicameral bone cyst, chondroblastoma, chondrosarcoma, chondromyxoid fibroma, Ewing’s tumour and metastatic carcinoma have all been reported to display similar imaging features as an ABC 1 4 5. A combination of both radiographs and MRI, alongside histological examination, is required to increase the likelihood of an accurate diagnosis 5…”
Section: Descriptionmentioning
confidence: 99%
See 2 more Smart Citations